2023
DOI: 10.3847/1538-4365/acee7f
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Associations between Supernova Remnants and Molecular Clouds

Xin Zhou,
Yang Su,
Ji Yang
et al.

Abstract: We universally search for evidence of kinematic and spatial correlation of supernova remnant (SNR) and molecular cloud (MC) associations for nearly all SNRs in the coverage of the Milky Way Imaging Scroll Painting CO survey, i.e., 149 SNRs, 170 SNR candidates, and 18 pure pulsar wind nebulae in 1° < l < 230° and −5.°5 < b < 5.°5. Based on high-quality and unbiased 12CO/13CO/C18O (J = 1–0) survey data, we apply automatic algorithms to identify broad lines and spatial correlations for molecular gas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 251 publications
(290 reference statements)
0
6
0
Order By: Relevance
“…The proper motion, now reduced in magnitude but with substantially less uncertainty, combined with the expansion of CTB 1 seem to be indicative of a fairly large ISM density. The implied value would be beyond the low density (∼0.1-1.0 cm −3 ) which has typically been inferred from the remnant's relatively weak Hα emission (Landecker et al 1982) or from the nondetection of tracers such as CO (Zhou et al 2023). While this can be somewhat mitigated if one assumes a weaker supernova energy (E 51 < 1), the collimation of the pulsar's bow shock is decoupled from this term and still requires a higher density given this lower velocity.…”
Section: Discussionmentioning
confidence: 93%
“…The proper motion, now reduced in magnitude but with substantially less uncertainty, combined with the expansion of CTB 1 seem to be indicative of a fairly large ISM density. The implied value would be beyond the low density (∼0.1-1.0 cm −3 ) which has typically been inferred from the remnant's relatively weak Hα emission (Landecker et al 1982) or from the nondetection of tracers such as CO (Zhou et al 2023). While this can be somewhat mitigated if one assumes a weaker supernova energy (E 51 < 1), the collimation of the pulsar's bow shock is decoupled from this term and still requires a higher density given this lower velocity.…”
Section: Discussionmentioning
confidence: 93%
“…Various distances d to the shell have been quoted: Yamaguchi et al (2004) divided their N H value of 5.2 × 10 22 cm −2 by an assumed mean interstellar medium hydrogen density of 1 cm −3 to obtain d = 17 kpc, while Kilpatrick et al (2016) used the velocity of broadened CO J = 2 -1 emission (∼+45 km s −1 ) seen toward the eastern shell of G32.4+0.1 to obtain 11.8-18.5 kpc from rotation curves. A cavity in 12 CO (1 -0) emission at a velocity of 10.8 km s −1 surrounding G32.4+0.1 was identified in a survey of firstquadrant SNRs (Sofue et al 2021), but the survey by Zhou et al (2023) found broad CO (1 -0) line features associated with G32.4+0.1 at a velocity giving d = 10.1 ± 0.4 kpc. Though an association of the shell and the pulsar is subject to question (see below), we shall use the pulsar distance of 11 kpc as the distance to the shell.…”
Section: G324+01mentioning
confidence: 99%
“…To our knowledge, there are no instances of SN implosions reported in observations. This might, however, simply attest to the fact that radiative SNRs, in particular those close to merging with the ISM, are very dim and thus are often difficult to observe (Green 2019; Koo et al 2020;Zhou et al 2023). Moreover, the fact that the morphology of imploding SNRs differs qualitatively from traditional SNRs might have led to a misclassification of imploding SNRs as something other than an SNR.…”
Section: Sn Implosion In the Literaturementioning
confidence: 99%